Oxidative brain damage in Mecp2-mutant murine models of Rett syndrome - De Felice, Claudio; Della Ragione, Floriana; Signorini, Cinzia; Leoncini, Silvia; Pecorelli, Alessandra; Ciccoli, Lucia; Scalabrì, Francesco; Marracino, Federico; Madonna, Michele; Belmonte, Giuseppe; Ricceri, Laura; De Filippis, Bianca; et al. (Neurobiology of disease, 2014)
Rett syndrome (RTT) is a rare neurodevelopmental disorder affecting almost exclusively females, caused in the overwhelming majority of the cases by loss-of-function mutations in the gene encoding methyl-CpG binding protein 2 (MECP2). High circulating levels of oxidative stress (OS) markers in patients suggest the involvement of OS in the RTT pathogenesis. To investigate the occurrence of oxidative brain damage in Mecp2 mutant mouse models, several OS markers were evaluated in whole brains of Mecp2-null (pre-symptomatic, symptomatic, and rescued) and Mecp2-308 mutated (pre-symptomatic and symptomatic) mice, and compared to those of wild type littermates. Selected OS markers included non-protein-bound iron, isoprostanes (F2-isoprostanes, F4-neuroprostanes, F2-dihomo-isoprostanes) and 4-hydroxy-2-nonenal protein adducts. Our findings indicate that oxidative brain damage 1) occurs in both Mecp2-null (both −/y and stop/y) and Mecp2-308 (both 308/y males and 308/+ females) mouse models of RTT; 2) precedes the onset of symptoms in both Mecp2-null and Mecp2-308 models; and 3) is rescued by Mecp2 brain specific gene reactivation. Our data provide direct evidence of the link between Mecp2 deficiency, oxidative stress and RTT pathology, as demonstrated by the rescue of the brain oxidative homeostasis following brain-specifically Mecp2-reactivated mice. The present study indicates that oxidative brain damage is a previously unrecognized hallmark feature of murine RTT, and suggests that Mecp2 is involved in the protection of the brain from oxidative stress. •Oxidative damage is demonstrated in the brain, and more specifically in the neurons, of Mecp2 mutant mouse models.•A direct evidence between enhanced oxidative stress and Mecp2 deficiency is provided.•Oxidative damage precedes the behavioral abnormalities in Mecp2 mutant mice.•Mecp2 is likely involved in the protection of the brain from oxidative stress.